Unilateral Isolated Pleural Effusion in Ovarian Hyperstimulation Syndrome - Ali Sami Gürbüz; Emel Ebru Özçimen; Necati Özçimen (Medical Network, 2016)
Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication with symptoms ranging from mild to severe. Pleural effusion occurs in severe forms of OHSS; however, isolated pleural effusion is rare. Here, we report a case of OHSS with isolated pleural effusion at presentation and discuss OHSS in light of the literature.